5-Aminolevulinic acid/sodium ferrous citrate improves the quality of heat-stressed bovine oocytes by reducing oxidative stress - Omnia ELGENDY; Go KITAHARA; Kentaro YAMADA; Shin TANIGUCHI; Takeshi OSAWA (The Society for Reproduction and Development, 2023)
A high temperature-humidity index during summer has deleterious effects on mitochondrial function, reducing oocyte developmental competence. 5-Aminolevulinic acid (5-ALA) and sodium ferrous citrate (SFC) are both known to support mitochondrial function and have strong anti-oxidant and anti-apoptotic activities. This study aimed to determine the mechanism of action of 5-ALA/SFC on oocyte quality. Bovine oocytes were collected from medium-sized follicles during summer (July-September, temperature-humidity index:76.6), cultured with 0, 1, 2, 4, and 8 µM 5-ALA with SFC at a molar ratio of 1:0.125, fertilized, and cultured for 10 days. The addition of 8/1 µM 5-ALA/SFC had a deleterious effect on oocyte cleavage rate in comparison with control oocytes, but did not affect the blastocyst rate, while 1/0.125 µM 5-ALA/SFC had a significantly higher increase in blastocyst rate than 8/1 µM 5-ALA/SFC. The addition of 1/0.125 and 2/0.25 µM 5-ALA/SFC improved oocyte quality by increasing the mitochondrial distribution pattern and metaphase-II oocytes, reducing reactive oxygen species and upregulating nuclear factor erythroid-2-related factor 2, heme oxygenase-1, and superoxide dismutase-1 in oocytes, and nuclear factor erythroid-2-related factor 2 and mitochondrial transcription factor A in cumulus cells. These results indicate that 1/0.125 and 2/0.25 µM 5-ALA/SFC may support oocyte quality and developmental competence and provide anti-oxidant actions in cumulus-oocyte complexes.